Music performance anxiety among music students in Malaysian universities / Fatin Hani Mohd Sheriff - Mohd Sheriff, Fatin Hani (2016)
This study investigates music performance anxiety (MPA) among bachelor degree music students in Malaysian universities, namely Universiti Teknologi MARA (UiTM), Universiti Pendidikan Sultan Idris (UPSI), Universiti Putra Malaysia (UPM) and Universiti Malaya (UM). The components of MPA constructs are: causes/situational factors, temporal occurrence, autonomic arousal, cognitive manifestations, affective manifestations, behavioral manifestations, and somatic manifestations. Respondents were chosen by using stratified random sampling and questionnaires were distributed to 300 music degree students of which 292 (97%) were returned. Data were statistically analysed which include descriptive statistics, independent-samples Mest, one-way analysis of variance (ANOVA) and Pearson's coefficient of correlation. The findings indicated that based on the mean score for various sub-scales of the Music Performance Anxiety Scale (MPAS), temporal occurrence was found to be the most occurent factor of music performance anxiety among music degree students followed by causes/situational factors as a distant second. MPA differ between male and female respondents with respect to somatic manifestation (p < 0.05). The perception on the seven dimensions differ between hours of practice with respect to affective manifestation, behavioural manifestation, autonomic arousal (p < 0.05, respectively), and somatic manifestation (p < 0.01). The perceptions on MPA also differ between respondents of different groups of instruments played with respect to affective manifestation, behavioural manifestation and somatic manifestation (p < 0.05). Furthermore, the perceptions on MPA differ between respondents who had performed more than 11 times, between 6-10 times or less than 6 times in a year with respect to all the seven (7) dimensions. Finally, a weak to moderate relationships exist between various dimensions of MPA construct, between hours of practice and between frequency of music performance in a year among music students. The findings of the study give insights and rich understanding of MPA to music performers, academicians, researchers and music students in Malaysian universities.